FUNGSI HUKUM ISLAM SEBAGAI KONTROL SOSIAL : (KORELASINYA SEBAGAI SARANA PEMBINAAN KARAKTER SUAMI ISTRI) - Said Syaripuddin Abu Baedah (El 'Ailaah, 2026)
The main topic discussed in this article is the function of Islamic law as a form of social control and its correlation as a means of fostering the character of husbands and wives. This article aims to: (1) describe the social dimensions of marriage in Islam, and (2) explain how Islamic law plays a role in maintaining and cultivating human morality, particularly within family life. This study is a descriptive literature review employing a multidisciplinary approach, including normative-juridical, maslahat (public interest), philosophical, and sociological approaches. The findings indicate that the social dimensions of marriage in Islam take various forms, including safeguarding human existence on earth, preserving honor and clarity of lineage, protecting society from moral decadence, preventing the spread of diseases (especially sexually transmitted diseases), and providing spiritual tranquility for human beings. The role of Islamic law in maintaining human morality can be observed through the regulation of criminal sanctions, particularly taʿzīr sanctions, in addition to ḥudūd and qiṣāṣ. Taʿzīr sanctions are punishments whose types and measures are not explicitly specified in the textual sources, but are left to the discretion of rulers or judges based on considerations of public welfare (maṣlaḥah). The imposition of taʿzīr sanctions aims to correct, educate, and rehabilitate offenders. The practice of religious teachings through a commitment to the enforcement of Islamic law in household life constitutes an important space for the expression of religious experience. Thus, Islamic law can truly serve as a comprehensive guide for human life, leading to the attainment of both spiritual and physical well-being, and to the realization of a harmonious individual and social order within the framework of raḥmatan li al-ʿālamīn.